2013
DOI: 10.1186/1742-4690-10-25
|View full text |Cite
|
Sign up to set email alerts
|

The V86M mutation in HIV-1 capsid confers resistance to TRIM5α by abrogation of cyclophilin A-dependent restriction and enhancement of viral nuclear import

Abstract: BackgroundHIV-1 is inhibited early after entry into cells expressing some simian orthologues of the tripartite motif protein family member TRIM5α. Mutants of the human orthologue (TRIM5αhu) can also provide protection against HIV-1. The host protein cyclophilin A (CypA) binds incoming HIV-1 capsid (CA) proteins and enhances early stages of HIV-1 replication by unknown mechanisms. On the other hand, the CA-CypA interaction is known to increase HIV-1 susceptibility to restriction by TRIM5α. Previously, the mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 69 publications
3
27
0
Order By: Relevance
“…In contrast, 4Mut substitutions did not alter the affinity for recombinant CypA, while 5Mut hexamer exhibited a 3-fold decreased affinity (41 M versus 12 M for WT and 4Mut). The latter effect is likely due to the H87P substitution in 5Mut CA, which results in the loss of a hydrogen bond between H87 in capsid and N71 in CypA and may alter the conformation of the CypA binding loop, as has been reported for a substitution at the adjacent position 86 (44).…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, 4Mut substitutions did not alter the affinity for recombinant CypA, while 5Mut hexamer exhibited a 3-fold decreased affinity (41 M versus 12 M for WT and 4Mut). The latter effect is likely due to the H87P substitution in 5Mut CA, which results in the loss of a hydrogen bond between H87 in capsid and N71 in CypA and may alter the conformation of the CypA binding loop, as has been reported for a substitution at the adjacent position 86 (44).…”
Section: Resultsmentioning
confidence: 94%
“…The mechanism by which CypA modulates the viral infectivity is complex and poorly understood, being dependent on the CA protein primary sequence and the host cell type (4)(5)(6). For example, it is known that mutations in the CypA-binding loop of the CA protein dramatically reduce virus infectivity (7,8). The A92E and G94D escape mutants bind CypA with similar affinity to wild-type CA, but exhibit only 10% of the activity of wild-type CA in the presence of CypA, and full infectivity can be restored if CypA is inhibited with cyclosporin A in the host cells (8), as shown schematically in SI Appendix, Fig.…”
mentioning
confidence: 99%
“…3). It was previously reported that V86M CA allows HIV-1 to escape from Rh (Pacheco et al, 2010) and mutant human TRIM5a (Veillette et al, 2013). On the other hand, virus harbouring only the V86E mutation exhibits decreased Rh TRIM5a sensitivity (Soll et al, 2013).…”
Section: Discussionmentioning
confidence: 96%